An Accurate Classification Method of Harmonic Signals in Power Distribution System by Utilising S-Transform - M. Hatta Jopri; A. Rahim Abdullah; Mustafa Manap; M. Faiz Habban; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper presents an accurate classification method of harmonic signal in power distribution system by using S-transform (ST).  ST has a capability of representing signals in jointly time-frequency domain and known as time frequency representation (TFR). The spectral parameters are estimated from TFR in order to identify the characteristics and to classify the harmonic signals. The classification of harmonic signals with the utilization of pattern recognition approach which is rule-based classifier of 100 unique signals is according to the IEEE standard 519:2014. The accuracy of the proposed method is determined by using MAPE and the results proved that the method provides high accuracy of harmonic signal classification. Additionally, S-transform also gives 100 percent correct classification of harmonic signals. It is proven that the proposed method is accurate in detecting and classifying harmonic signals in the distribution system.